Estimation of Strong Wind Distribution on the Korean Peninsula for Various Recurrence Periods: Significance of Nontyphoon Conditions - Jae-Hee Hahm; Ha-Yoon Jeong; Kyung-Hwan Kwak (Advances in Meteorology)
Long-term automated synoptic observing system (ASOS) data collected from 101 stations over a period of 50 years (1967–2016) were analyzed to investigate the distribution of strong winds on the Korean peninsula by utilizing a statistical method. The Gumbel distribution was used to estimate the wind speed for recurrence periods of 1, 10, 50, 75, and 100 years. For all recurrence periods, the coastal regions experienced higher wind speeds, which exceeded the strong wind advisory level, than the inland and metropolitan regions. The strong winds were predominantly induced by summertime typhoons, especially in the south and west coastal regions. In addition, nontyphoon factors, such as a topographical factor with atmospheric instability in a mountainous coastal region, can cause localized severe weather in the form of strong wind. By performing the weather research and forecasting (WRF) model simulation, an abrupt increase in wind speed up to 20 m·s−1 was reproduced under the condition of onshore prevailing winds heading toward a mountain ridge in a coastal region. Estimation of strong wind spatial distribution can help the region-to-region establishment of an action plan to prepare for damage caused by strong winds.